Constitutional Court Decision as Market Signal: An Empirical Study of Insurance Sector Stocks in Indonesia - Ghiyats Furqan Dewantara; Saras Shinta Qurrota Aini; Aditya Kumala Dewi; Afif Musthafa (Center of Economic Students Journal, 2025)
This study analyses the impact of the Constitutional Court (MK) Decision No. 83/PUU-XXII/2024 on investor reactions to insurance-sector stocks in Indonesia. This decision revises Article 251 of the Commercial Code (KUHD), which previously allowed insurance companies to cancel policies even if misinformation occurred without intent. This change could affect risk perceptions and investor expectations regarding claim obligations. This event study employs two statistical tests: the Wilcoxon signed-rank test to measure abnormal returns and the Generalized Sign Test for abnormal trading volume. The results show a significant decline in Cumulative Average Abnormal Return (CAAR) across all event windows. Furthermore, Cumulative Average Abnormal Trading Volume (CAATV) also declined significantly, reflecting weakening investor interest. These findings confirm that the market views the MK decision as increasing operational and financial risks for insurance companies.